2018
DOI: 10.1016/j.kint.2018.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Androgen exposure potentiates formation of intratubular communities and renal abscesses by Escherichia coli

Abstract: Females across their lifespan and certain male populations are susceptible to urinary tract infections (UTI). The influence of female vs. male sex on UTI is incompletely understood, in part because preclinical modeling has been performed almost exclusively in female mice. Here, we employed established and new mouse models of UTI with uropathogenic Escherichia coli (UPEC) to investigate androgen influence on UTI pathogenesis. Susceptibility to UPEC UTI in both male and female hosts was potentiated with 5α-dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 86 publications
6
61
1
Order By: Relevance
“…In the present work, we utilized non-refluxing C57BL/6 mice, which develop pyelonephritis of more modest severity after UPEC inoculation of the bladder. As we reported in the C3H background (Olson et al, 2016(Olson et al, , 2018, androgen exposure was here found also to increase the rate of high-titer pyelonephritis in C57BL/6 mice. Compared with the extensive scars formed in UPEC-infected C3H mice (Olson et al, 2017), the BL/6 background enabled us to model of more limited renal scar formation, without overwhelming inflammation, and offers many more readily available genetic tools to enable future investigation.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the present work, we utilized non-refluxing C57BL/6 mice, which develop pyelonephritis of more modest severity after UPEC inoculation of the bladder. As we reported in the C3H background (Olson et al, 2016(Olson et al, , 2018, androgen exposure was here found also to increase the rate of high-titer pyelonephritis in C57BL/6 mice. Compared with the extensive scars formed in UPEC-infected C3H mice (Olson et al, 2017), the BL/6 background enabled us to model of more limited renal scar formation, without overwhelming inflammation, and offers many more readily available genetic tools to enable future investigation.…”
Section: Discussionsupporting
confidence: 89%
“…Tgfb1 transcription was increased in TC‐treated mice early in infection, with elevated TGFβ1 production observed in TC‐treated mice was most evident in epithelial cells, predominantly in the distal nephron, earlier in infection (up to 7 dpi) and then in non‐epithelial (CD45−, E‐cadherin−) cell types later in infection (7–28 dpi). This sequence is logical, as renal epithelial surfaces are likely contacted earliest by UPEC during ascending infection (Li et al, 2017; Olson et al, 2018). Thus, epithelial TGFβ1 signaling is likely the initiator of the fibrotic response to infection; in other models, TGFβ1 signaling from epithelial cells alone is sufficient to drive a fibrotic response to injury (Gentle et al, 2013; Olson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations